Metastatic rhabdomyosarcoma of breast: A rare presentation (Indian Journal of Case Reports, 2020)
Rhabdomyosarcoma (RMS) is the most common pediatric soft-tissue sarcoma with head and neck as the preferred site followed by the genitourinary system in 13–17 years. It can involve the breast as either primary or secondary. A multidisciplinary treatment approach of chemotherapy or radiotherapy or mastectomy depends on the clinical profile of the patient. Embryonal RMS has a better prognosis than alveolar and pleomorphic subtypes. Here, we report the case of a 17-year-old girl who is a known case of primary embryonal RMS of the right maxillary antrum diagnosed 2 years back and administered neoadjuvant chemotherapy followed by radiotherapy-concurrent chemoradiotherapy. Later, she developed right breast lump, which on fine-needle aspiration cytology (FNAC) of the lump showed characteristic features of metastatic RMS, thus avoided surgical intervention of lumpectomy or mastectomy. The patient received adjuvant chemotherapy followed by radiotherapy and is doing well. The aim of the present case is to assess the safer, faster role of FNAC in the diagnosis of breast RMS. It is also recommended to include ultrasound/mammography of the breast as a protocol in the metastatic workup of RMS for adolescent females.